2011
DOI: 10.1016/j.breast.2011.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer treatment and work disability: Patient perspectives

Abstract: The different experiences will require different types of support, especially concerning communication around disability and returning to work. Our findings highlight the need of an individual approach of the management of work disability for breast cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
58
0
21

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(83 citation statements)
references
References 13 publications
4
58
0
21
Order By: Relevance
“…In particular, they were neither told nor they themselves requested for rehabilitation care for the experienced discomfort. In accordance with previous studies [43,44], many women tried to handle their bothers either by changing the usual way in which they carried out an activity, by modifying their work schedule, or by eliminating tasks considered too diicult to perform. The relatively lack of assistance from spouse, family members, or friends to carry out daily activities also needs to be considered, as it can afect the interaction of this women with their family and social environment [43].…”
Section: Discussionsupporting
confidence: 70%
“…In particular, they were neither told nor they themselves requested for rehabilitation care for the experienced discomfort. In accordance with previous studies [43,44], many women tried to handle their bothers either by changing the usual way in which they carried out an activity, by modifying their work schedule, or by eliminating tasks considered too diicult to perform. The relatively lack of assistance from spouse, family members, or friends to carry out daily activities also needs to be considered, as it can afect the interaction of this women with their family and social environment [43].…”
Section: Discussionsupporting
confidence: 70%
“…A general answer seems hard to give because of the large variation in experiences. In an earlier study [4] we found that the experiences of women (employees) as regards being work disabled due to breast cancer varied widely. Three main types of experiences were distinguished: a 'disruption' with irreparable loss, an 'episode' after which life continues as before, and a 'meaningful period' after which new life priorities are set.…”
Section: Discussionmentioning
confidence: 97%
“…Three main types of experiences were distinguished: a 'disruption' with irreparable loss, an 'episode' after which life continues as before, and a 'meaningful period' after which new life priorities are set. Perhaps only the women who experience their breast cancer period as an episode might be capable of initiating straightforward RTW [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative research is needed to explore how RTW is experienced, and this research focuses on both the phases preceding actual RTW and that after actual RTW. Previous qualitative research showed that breast cancer patients experienced their work disability in numerous different ways, highlighting the need for an individual approach to the management of sickness absence [11]. During their absence from work, they further appeared to mentally prepare their RTW by considering carefully how to make the transition from being ill to returning to work [12].…”
Section: Introductionmentioning
confidence: 98%